Pemanfaatan Aplikasi Linktree Sebagai Media Pembelajaran Pendidikan Agama Pada Guru MTs N 5 Kabupaten Mandailing Natal - Endar Muda Halomoan; Zulhimma; Hamdan Hasibuan (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2024)
Utilization is the process of making something more beneficial. In this study, utilization refers to how students use the time provided by teachers to access religious websites. The Linktree application is a platform that integrates various links into a single page, making learning easier for users. The advantages of Linktree include ease of operation, display management, as well as adding and removing links. This application can be used for learning evaluations such as quizzes, matching exercises, and short essays. According to Zaccaria, Linktree is an optimal alternative for learning. This research is qualitative, focusing on the utilization of learning media at MTs N 5 Kabupaten Mandailing Natal. Linktree enriches teachers' and students' knowledge in using online media. Religious teachers use it to develop students' character through active interaction. Additionally, Linktree serves as a solution for students who fall behind in their studies. As an interactive tool, teachers can set learning boundaries in an online format. Remedial learning through Linktree allows students to reach the expected minimum competency standards. Thus, this application is an innovation in enhancing learning effectiveness in the school environment.